THE PHENOMENON OF MARKETING STRATEGIES IN DIGITAL ERA TODAY - Reza Muhammad Ramdani; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
Marketing strategy changes need to be made to face challenges in the digital era. The main factor influencing changes in marketing strategy is changes in consumer behavior. Organizations must change their methods of understanding consumer preferences and desires because consumers now have greater access to information through the internet and social media. The purpose of this study is to analyze what phenomena change marketing strategies in facing challenges in the digital era. The research method is a literature study. The results of this study are Marketing strategies must be innovative and creative because they change consumer behavior, industry problems, and assess technological advances. In the digital era, managing change is very important to overcome challenges and take advantage of opportunities. In addition, the government encourages business owners to use technology to help their company management procedures succeed in today's very tight digital market by using creative and data-based marketing methods. Organizations are expected to be able to manage change effectively, adopt new technologies, and take advantage of new possibilities. Future business success depends not only on mastery of technology, but also on the ability to innovate, adapt, and have comprehensive understanding of market dynamics.